2016
DOI: 10.1186/s40360-016-0083-8
|View full text |Cite
|
Sign up to set email alerts
|

The synergy and mode of action of quercetin plus amoxicillin against amoxicillin-resistant Staphylococcus epidermidis

Abstract: BackgroundStaphylococcus epidermidis is one of the most multiple resistances to antibiotics in the recent years. Therefore, practically-prescribed antibiotics in the treatment of these strains are not effective. Plant-derived antibacterial is one of the most interesting sources of new therapeutics. The present study was to investigate antibacterial, synergy and modes of action of quercetin and amoxicillin against amoxicillin-resistant Staphylococcus epidermidis (ARSE).MethodsThe MICs, checkerboard assay, viabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(59 citation statements)
references
References 45 publications
2
53
0
4
Order By: Relevance
“…epidermidis were assessed. The results indicated that upon combination of quercetin and amoxicillin, the synergistic activity was observed and bacterial resistance to this traditional antibiotic was remarkably reversed (Siriwong, Teethaisong, Thumanu, Dunkhunthod, & Eumkeb, ).…”
Section: Antibacterial Activity Of Flavonoidsmentioning
confidence: 99%
“…epidermidis were assessed. The results indicated that upon combination of quercetin and amoxicillin, the synergistic activity was observed and bacterial resistance to this traditional antibiotic was remarkably reversed (Siriwong, Teethaisong, Thumanu, Dunkhunthod, & Eumkeb, ).…”
Section: Antibacterial Activity Of Flavonoidsmentioning
confidence: 99%
“…[ 155 ] There is already evidence for the enhancement of conventional antibiotics by acting synergistically with plant-derived compounds. The combination of β-lactams with a-mangostin isolated from mangosteen fruit,[ 156 157 ] or with quercetin or kaempferol from various fruits, vegetables, and grains,[ 158 ] substantially increase the efficacy of the therapy in β-lactam resistant bacterial strains. It is likely that the mangosteen derived components of these combinations may inhibit the bacterial β-lactamase enzyme, thus reactivating the antibiotic.…”
Section: Combinational Antimicrobial Chemotherapiesmentioning
confidence: 99%
“…There has been significant recent interest in combination therapy, combinations of antibiotics with other antibiotics, peptides and plant extracts, to increase antibiotic efficacy [19,20].…”
Section: Assessment Of Antibiotic Interactions Showed That Honey Was mentioning
confidence: 99%